Let and be the roots of the equation , and and be the roots of the equation , with and are non-zero real integers. Find the value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
c and d are the roots of the equation x 2 + a x + b = 0 , then c + d = − a and c d = b
a and b are the roots of the equation x 2 + c x + d = 0 , then a + b = − c and a b = d
c + d = − a → a + c = − d . . . ( 1 )
a + b = − c → a + c = − b . . . ( 2 )
We can clearly see that ( 1 ) = ( 2 ) .
Since b and d are not equal to zero, we can easily conclude that b = d .
c d = b → c = 1 .
a b = d → a = 1 .
c + d = − a ⇒ 1 + d = − 1 → d = b = − 2 .
Hence, we have a + b + c + d = 1 + 1 − 2 − 2 = − 2 .